Choice of intrathecal drug in the treatment of neuropathic pain – new research and opinion. Issue 10 (3rd October 2019) - Deer, Timothy R.; Malinowski, Mark; Varshney, Vishal; Pope, Jason
ABSTRACT: Introduction : The choice of the proper intrathecal drug to treat neuropathic pain has been subject to much debate in recent years. Areas Covered : Currently, the United States Food and Drug Administration (USFDA) has approved two drugs for chronic intrathecal use for the treatment of pain; however, there has been substantial growth in the development of other intrathecal drugs that can be used for neuropathic pain. We performed a PubMed literature search looking at intrathecal drug research for neuropathic pain between January 2005 to May 2019 and discuss current practices and mechanisms in treating these complex patients. Expert Opinion : On-label intrathecal drugs are recommended if efficacious with acceptable side effects. In those suffering from neuropathic pain, clinical evidence suggests additional drug algorithms for treating these patients are necessary. There is ample room for growth in the development and approval of novel drugs for intrathecal delivery to manage neuropathic pain.